Diabetic Retinopathy in Type 2 Diabetics - Khurram, Muhammad; Javed, Munaza; Faheem, Muhammad; Bushra, Hamama Tul (Journal of Rawalpindi Medical College, 2026)
Background: To determine the frequency of diabetic retinopathy (DR) and its association with age, gender, duration of illness and type of anti diabetic treatment in type 2 diabetic patients. Methods: In this cross sectional study 225 type 2 diabetes mellitus patients underwent detailed fundus examination for presence or absence of DR. If DR was noted, it was classified into background retinopathy, pre-proliferative retinopathy, proliferative retinopathy, and maculopathy. Comparison of patients with and without DR was done in terms of mean age, gender, duration of diabetes mellitus, and predominant mode of treatment (insulin or oral hypoglycemic agents) employing t test or Chi2 test wherever appropriate. Duration of diabetic illness and type of DR were also correlated similarly. Results: Mean patient age was 57.52±9.77 years. Diabetic retinopathy was seen in 52.4%. Majority (74.7%) were on oral hypoglycemics and 25.3% were on insulin. In 29.3% patients duration of diabetic illness was 5-10 years, while in the rest it was >10 years. Non-proliferative retinopathy was seen in 37.3%, 31.4% had pre-proliferative retinopathy, 10.2% had proliferative retinopathy and 21.2% had maculopathy. Longer duration of diabetes had statistically significant association with presence of DR and type of DR (p <0.05). Insulin therapy also correlated with presence of DR (p <0.05). Conclusion: Frequency of DR in our type 2 DM patients was 52.4%. Duration of diabetic illness, and insulin therapy correlate with presence of DR. Key Words: Diabetes Mellitus, Retinopathy.